The effect of different doses of esmolol on hemodynamic, bispectral index and movement response during orotracheal intubation: prospective, randomized, double-blind study - Çakırgöz,Mensure Yılmaz (2014)
Objective: A prospective, randomized and double-blind study was planned to identify the optimum dose of esmolol infusion to suppress the increase in bispectral index values and the movement and hemodynamic responses to tracheal intubation. Materials and methods: One hundred and twenty patients were randomly allocated to one of three groups in a double-blind fashion. 2.5 mg kg-1 propofol was administered for anesthesia induction. After loss of consciousness, and before administration of 0.6 mg kg-1 rocuronium, a tourniquet was applied to one arm and inflated to 50 mm Hg greater than systolic pressure. The patients were divided into 3 groups; 1 mg kg-1 h-1 esmolol was given as the loading dose and in Group Es50 50 μg kg-1 min-1, in Group Es150 150 μg kg-1 min-1, and in Group Es250 250 μg kg-1 min-1 esmolol infusion was started. Five minutes after the esmolol has been begun, the trachea was intubated; gross movement within the first minute after orotracheal intubation was recorded. Results: Incidence of movement response and the ΔBIS max values were comparable in Group Es250 and Group Es150, but these values were significantly higher in Group Es50 than in the other two groups. In all three groups in the 1st minute after tracheal intubation heart rate and mean arterial pressure were significantly higher compared to values from before intubation (p < 0.05). In the study period there was no significant difference between the groups in terms of heart rate and mean arterial pressure. Conclusion: In clinical practise we believe that after 1 mg kg-1 loading dose, 150 μg kg-1 min-1 iv esmolol dose is sufficient to suppress responses to tracheal intubation without increasing side effects.